2022
DOI: 10.1017/s0007114522001040
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of racial/ethnic variation in the association between change in cystatin C and dietary quality in older Americans

Abstract: Using a sample of U.S. adults aged 65 and older, we examined the role of dietary quality in cystatin C change over 4 years and whether this association varied by race/ethnicity. The Health and Retirement Study provided observations with biomarkers collected in 2012 and 2016, participant attributes measured in 2012, and dietary intake assessed in 2013. The sample was restricted to respondents who were non-Hispanic/Latino White (n = 789), non-Hispanic/Latino Black (n = 108), or Hispanic/Latino (n = 61). Serum cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Recent research on nutrition in KTRs has focused on the intake of nutrients or foods and how this relates to control of complications [ 22 24 ]. Two US longitudinal studies have shown that diet quality seems to be associated with serum Cys in the elderly, with high-quality diets leading to healthier serum cystatin C outcomes, but less research has been conducted on the relationship between diet quality and serum Cys in KTRs [ 25 , 26 ]. Studies have shown that due to the complexity of diets, dietary quality is a more reliable nutritional monitoring indicator than nutrition [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on nutrition in KTRs has focused on the intake of nutrients or foods and how this relates to control of complications [ 22 24 ]. Two US longitudinal studies have shown that diet quality seems to be associated with serum Cys in the elderly, with high-quality diets leading to healthier serum cystatin C outcomes, but less research has been conducted on the relationship between diet quality and serum Cys in KTRs [ 25 , 26 ]. Studies have shown that due to the complexity of diets, dietary quality is a more reliable nutritional monitoring indicator than nutrition [ 27 ].…”
Section: Introductionmentioning
confidence: 99%